Construction and validation of checklist for disinfection of ambulances for transporting patients Covid-19 - Alexandre, Ana Carla Silva (2021)
ABSTRACTPurpose: To build and validate a checklist for disinfecting ambulances transporting patients with Covid-19.Method: A methodological study composed of the construction of a checklist and validation by 42 professionals, of which 35 professionals had expertise in patient transport / transfer and seven in hospital infection control. The item with a minimum agreement of 80% has considered valid, based on the Content Validation Index and binomial test.Results: The checklist had the steps performed for terminal disinfection of ambulances. It had 54 items, which included the individual protection equipment and materials used, disinfection of the driver's cabin, equipment and the patient care cabin. The minimum agreement obtained was 85% and the average of the Content Validation Index was 0.96.Conclusion: Was the checklist considered valid in terms of content and can be used to disinfect ambulances transporting patients with Covid-19.Keywords: Coronavirus infections. Disinfection. Validation study. Ambulances.